2019
DOI: 10.30538/oms2019.0086
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-valuations and pseudo-metric on JU-algebras

Abstract: In this paper we have introduced the concept of pseudo-valuations on JU-algebras and have investigated the relationship between pseudo-valuations and ideals of JU-algebras. Conditions for a real-valued function to be a pseudo-valuation on JU-algebras are given and results based on them have been shown. We have also defined and studied pseudo-metric on JU-algebras and have proved that ϑ being a valuation on a JU-algebras A, the operation in A is uniformly continuous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Therefore, it is important to investigate social commerce adoption by SMEs. However, insufficient empirical studies have been conducted on the extent to which SMEs have adopted social commerce (Abed, 2020;U. Ali et al, 2019;Alraja et al, 2020;Sharma et al, 2020), particularly in developing countries such as Jordan.…”
Section: Significance Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is important to investigate social commerce adoption by SMEs. However, insufficient empirical studies have been conducted on the extent to which SMEs have adopted social commerce (Abed, 2020;U. Ali et al, 2019;Alraja et al, 2020;Sharma et al, 2020), particularly in developing countries such as Jordan.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Prior research has shown that SMEs are also falling behind large firms regarding IT adoption (Abed, 2020;U. Ali et al, 2019;Chatterjee & Kar, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In this section, we take the definitions of JU-algebras, JU-subalgebras, JU-ideals and other important terminologies and some related results from literature [7,8].…”
Section: Preliminariesmentioning
confidence: 99%
“…In [7,8], the concept of JU-algebras is introduced and analyzed. However, this concept was introduced earlier in [9] under the name 'pseudo KU-algebra'.…”
Section: Definitionmentioning
confidence: 99%
See 1 more Smart Citation